The effect of sales promotions characteristics on brand equity - Bahram Jabarzadeh Karbasi; Ali Jafari Rad (Management Science Letters)
In the recent years, retail industry in Iran has faced an increasing competition and this has encouraged the managers of chain stores to find ways to differentiate their own companies. One of the influential factors in this field is brand equity. Concerning this issue, the aim of this paper is to examine the effectiveness of sale promotions on the brand equity of ETKA chain stores. Therefore, a sample of 500 people among the customers of these stores in Tehran was examined. The achieved information obtained from the questionnaire was analyzed through structural equation modeling. The results showed that monetary and non-monetary promotions could influence on brand association, brand awareness and the perceived quality. On the other hand, it came out that brand association and the perceived quality are influential on brand loyalty. At last, a few suggestions were presented based on the results of this research.